A CHARACTERISTIC LOCALIZATION OF BACILLUS ABORTUS IN THE BOVINE FETAL MEMBRANES - Smith, Theobald (The Rockefeller University Press, 1919)
The significance of this invasion of the chorionic epithelium from the standpoint of pathogene'sis cannot be properly evaluated until a more complete history of the successive localizations of Bacillus abortus has been obtained. It is safe to assume that this particular cell parasitism is but one of a series of localizations and centers of multiplication in the fetal membranes although evidence points to it as perhaps the earliest stage in which the organism gains by rapid, unchecked multiplication a considerable advantage over the host. The local destruction of an epithelial covering by an infectious agent when other miscellaneous infectious agents are absent may or may not be of much importance, for it would depend on the regenerative activity of the epithelium, the tendency to the gathering of injurious transudates, and the toxic substances associated with the bacilli. It is probable that localizations also occur in the walls of the blood vessels of the chorion. Thus far only one case of this kind has been observed. The fusiform connective tissue cells of the adventitious coat of a blood vessel 0.8 mm. in diameter were completely replaced by clumps of minute bacilli. Since there is usually a slight perivascular cell infiltration in the diseased placenta this localization may be largely responsible for the circulatory disturbances which lead to death of the fetus. The case referred to may be but a greatly exaggerated illustration of the action of Bacillus abortus in the walls of the blood vessels where they are too few in number at any one time to be identified. It is known, that in the guinea pig disease with pronounced lesions Bacillus abortus is demonstrated only with great difficulty because of its scarcity. The more or less specific localization and multiplication of bacteria within cells not having phagocytic functions have thus far been demonstrated in leprosy, syphilis, and in a disease of mice recently described by Tyzzer, who found an active invasion of both liver cells and intestinal epithelium by a bacillus. In cells to which phagocytic powers have been ascribed the specific localization of certain bacteria is well known. Thus tubercle bacilli occur within the endothelial cells of the tubercle. Leprosy bacilli have been found within a variety of cell groups. Mouse septicemia bacilli occur regularly within certain phagocytic cells of the blood. Recently bacteria have been found attached to the cilia of the respiratory tract in pertussis by Mallory and Hornor, in a form of guinea pig pneumonia by the writer. Actual occupation of epithelial cells followed by active multiplication of the invaders and destruction of the cell has, however, been frequently demonstrated for the sporozoa. That it may occur more often among bacteria is highly probable. Rapidity of multiplication and cell destruction or invisibility or both may stand in the way of a satisfactory demonstration.